Shark finning in eastern Indonesia: assessing the sustainability of a data-poor fishery. (7th November 2016) - Jaiteh, Vanessa F.; Hordyk, Adrian R.; Braccini, Matías; Warren, Carol; Loneragan, Neil R.
Abstract : For over two decades, Indonesia has reported higher average shark landings than any other nation, but very little local information exists on the fishery and life histories of targeted species. This poses severe challenges to shark sustainability and conservation in this vast archipelago. We draw on diverse sources of data to evaluate the sustainability of the shark fishery in eastern Indonesia, a particularly data-poor region where sharks are primarily targeted for their fins. Shark fishers from three coastal communities were interviewed on their perceptions of catch trends over the past twenty years and asked to collect fishing data during fishing trips in the Seram, Arafura and Timor Seas. For the most frequently harvested species, we estimated maximum intrinsic rates of increase ( r max ) to predict their resilience to fishing pressure. Our results indicate that shark fishing practices in the region are likely to be unsustainable. The catches of several species largely comprised of immature individuals and most fishers attributed observed declines in shark numbers, size and species diversity to overfishing. Hammerhead sharks have relatively high intrinsic resilience but are nevertheless at risk of local extinction due to their availability to the fishery and the value of their fins. Sandbar, dusky and grey reef sharks have lower resilience and are frequently caught but not managed. We recommend a composite management approach, including consistent implementation of existing trade restrictions, fisheries research and opportunities for fishers' livelihood diversification, to stem shark harvests in eastern Indonesia.